Volunteers' Perceptions of the Economic Impact of the MBG Kitchen on Employment Generation Locally - Muhammad Erfan Aziz; R. Ayu Erni Jusnita; Nurul Suhesti (Westscience Press, 2026)
The Free Nutritious Meal (MBG) Program has attracted attention for its socio-economic impact beyond food provision. This study examines volunteers’ perceptions of the economic impact of the MBG kitchen at SPPG Nginden Jangkungan, Surabaya, particularly regarding local employment generation. A qualitative phenomenological approach was employed using semi-structured interviews, participant observation, and documentation. The findings identified four themes. First, the MBG kitchen creates employment opportunities and additional income for housewives, unemployed youth, and informal workers. Second, collective activities strengthen social solidarity, cooperation, and community participation. Third, involvement in the program enhances volunteers’ self-confidence, empowerment, and social identity. Fourth, limited facilities, uneven task allocation, and inadequate institutional support challenge program sustainability. The study concludes that the MBG kitchen functions as both an economic empowerment mechanism and a social capital-building platform. Strengthening local recruitment, volunteer capacity development, operational support, and stakeholder collaboration is recommended to sustain and expand the program’s socio-economic benefits.